Mediterranean diet and mental health in university students: an Italian cross-sectional study. (30th September 2020) - Corezzi, M; Bert, F; Lo Moro, G; Buda, A; Gualano, M R; Siliquini, R
Abstract: Background: Well-being is essential for positive mental health among university students, influencing their later attitudinal and career outcomes. Many factors contribute to endanger students' mental health, including academic stressors, as well as unhealthy lifestyles. Following a Mediterranean diet (MD), widespread in Europe, is proved to have a protective role for mental health. Our aim was to investigate mental well-being and adherence to the MD in university students. Methods: In 2019, a cross-sectional study was performed in Turin, Italy. Totally, 502 university students were enrolled. A socio-demographic form, the Mediterranean Diet Adherence Screener (MEDAS) and Warwick-Edinburgh Mental Wellbeing Scale (WEMBS), were used. Mainly, multivariable linear and logistic regressions were performed to investigate potential predictors of adherence to the MD and of psychological well-being (p < 0.05 considered significant). Results: The 24% of the sample resulted at high risk of depression (WEMWBS score<40) and the 22.7% at high risk of psychological distress (WEMWBS score 41-45). The median MEDAS score was 6 (IQR=2, non-normal distribution) in a possible range between 0 and 14 (the higher is the score, the higher is the adherence). Preliminary results showed that a MEDAS score ≥6 was associated to a lower risk of depression (OR = 0.78, p = 0.006). Not being on time with university exams (OR = 2.65, p = 0.002) and not having an excellent health status (OR = 1.94, p = 0.23) led to a higher depression risk instead. The main variables that had a negative association with MD adherence were WEMWBS<40 (coef=-0.65, p = 0.001) and not cooking personally (coef=-0.30, p = 0.04). Conclusions: Students who reported greater adherence to the MD were those with the lowest risk of depression. The potential protective role that MD has for mental health in young adults could be used to help developing more comprehensive intervention strategies of health promotion among European university students. Key messages: Adherence to the Mediterranean diet and good mental health seem to be related in a sample of university students analyzed through multivariable regressions. European policies and strategies addressing unhealthy lifestyles and encouraging Mediterranean diet adherence could be useful to improve well-being and mental health of university students.